Pengaruh Strategi Manufaktur terhadap Kinerja (Studi pada Industri Manufaktur Menengah dan Besar di Yogyakarta) - Abdul Ghofar Syarif Alam Sudin (Universitas Kristen Maranatha, 2004)
This research was examined the relationship between manufacturing strategy and firms performance. The most widely adopted strategy among medium and large manufacturing firms in Yogyakarta are quality strategy, cost strategy, delivery strategy and flexibility strategy. The significant relationship between manufacturing strategies and performance of an organization. This research found that Yogyakarta manufaturing firm that adopt quality strategies can achieve better performance in term of financial performance and firms that emphasize more on flexibility strategy can achieve better manufacturing performance. The findings of this study support the fact that manufacturing strategy can be practiced in Yogyakarta. The findings of this study also implies that an appropriate manufacturing strategy is required to ensure high performance.Key words: manufacturing strategy, cost strategy, quality strategy, flexibility strategy, delivery strategy and performance.